Reconciliation of essential process parameters for an enhanced predictability of Arctic stratospheric ozone loss and its climate interactions - von Hobe, M.; Bekki, S.; Borrmann, Stephan; Cairo, F.; D'Amato, F.; Di Donfrancesco, G.; Dörnbrack, Andreas; Ebersoldt, A.; Ebert, M.; Emde, C.; Engel, I.; Ern, M.; et al. (Atmospheric Chemistry and Physics, 2013)
Significant reductions in stratospheric ozone occur inside the polar vortices each spring when chlorine radicals produced by heterogeneous reactions on cold particle surfaces in winter destroy ozone mainly in two catalytic cycles, the ClO dimer cycle and the ClO/BrO cycle. Chlorofluorocarbons (CFCs), which are responsible for most of the chlorine currently present in the stratosphere, have been banned by the Montreal Protocol and its amendments, and the ozone layer is predicted to recover to 1980 levels within the next few decades. During the same period, however, climate change is expected to alter the temperature, circulation patterns and chemical composition in the stratosphere, and possible geo-engineering ventures to mitigate climate change may lead to additional changes. To realistically predict the response of the ozone layer to such influences requires the correct representation of all relevant processes. The European project RECONCILE has comprehensively addressed remaining questions in the context of polar ozone depletion, with the objective to quantify the rates of some of the most relevant, yet still uncertain physical and chemical processes. To this end RECONCILE used a broad approach of laboratory experiments, two field missions in the Arctic winter 2009/10 employing the high altitude research aircraft M55-Geophysica and an extensive match ozone sonde campaign, as well as microphysical and chemical transport modelling and data assimilation. Some of the main outcomes of RECONCILE are as follows: (1) vortex meteorology: the 2009/10 Arctic winter was unusually cold at stratospheric levels during the six-week period from mid-December 2009 until the end of January 2010, with reduced transport and mixing across the polar vortex edge; polar vortex stability and how it is influenced by dynamic processes in the troposphere has led to unprecedented, synoptic-scale stratospheric regions with temperatures below the frost point; in these regions stratospheric ice clouds have been observed, extending over ...